The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/dmso.s335731
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Diabetes Patients’ Self-Care Practices in Eastern Ethiopia: A Qualitative Study from the Health Care Providers Perspective

Abstract: Background All types of diabetes can damage the heart, blood vessels, eyes, kidneys, nerves and increase the overall risk of disability and premature death. Diabetes mellitus requires a range of self-care practices, scientifically recommended to control the glycemic level and maintain the patient’s health. However, perceived barriers that hinder patients from fully implementing these diabetes self-care practices and obstacles have not been thoroughly explored. Therefore, this study aimed to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Nevertheless, the full integration of exercise into routine healthcare in Africa is challenged by poor knowledge and attitudes of patients and healthcare providers [ 127 ]. In the same way, self-management of diabetes is poor in Africa as it faces numerous barriers [ 128 , 129 ]. Peer-support interventions have been increasingly recognized worldwide, but one may note that the transferability of interventions across different cultures might be difficult [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the full integration of exercise into routine healthcare in Africa is challenged by poor knowledge and attitudes of patients and healthcare providers [ 127 ]. In the same way, self-management of diabetes is poor in Africa as it faces numerous barriers [ 128 , 129 ]. Peer-support interventions have been increasingly recognized worldwide, but one may note that the transferability of interventions across different cultures might be difficult [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that when people were more educated improves people’s dietary adherence [ 65 ], and low educated level linked with inadequate glycemic controls [ 66 ]. Scholars identified that people with lower levels of education consume sugar- and fat-rich foods more often and fruit and vegetables less often than adults with a high education level [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otter and colleagues described how nurses with a limited understanding of the self-management concept attempted to persuade patients to follow their advice [ 27 ]. Traditionally, the medical model of care was founded upon patient compliance [ 28 ] rather than patient adherence to a collaborative plan of action [ 29 ]. Our nurses did not discuss approaches central to the nurses’ role in supporting DSM behaviors, such as assessing patient motivations [ 26 ], forming a nurse–patient relationship with empathetic and purposeful communications, or partnering with patients to meet specific goals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%